2022
DOI: 10.1111/jfbc.14060
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species: Key players in the anticancer effects of apigenin?

Abstract: Reactive oxygen species (ROS) exhibit a double-edged sword in cancer-hence their modulation has been an attractive strategy in cancer prevention and therapy. The abundance of scientific information on the pro-oxidant effects of apigenin in cancer cells suggests the crucial role of ROS in its mechanisms of action. Although apigenin is known to enhance the cellular ROS levels to cytotoxic degrees in cancer cells in vitro, it remains to be determined if these pro-oxidant effects prevail or are relevant in experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 156 publications
(155 reference statements)
0
7
0
Order By: Relevance
“…Although some cell culture studies and animal studies suggest that antioxidants can be used to fight oxidative damage hence decelerating the aging process, it is imperative to test those hypotheses in a clinical trial. 331 A recent study of 2570 women aged between 18 and 79 years found that Vitamin E is effective to maintain and grow higher skeletal muscle mass, which can eventually prevent sarcopenia. 332 Another randomized clinical trial conducted on 334 human beings suggested that Mediterranean diets containing olive oil and nuts can slow down age-related cognitive decline and decelerate the risk of developing dementia.…”
Section: Clinical Trial Of Antioxidantmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some cell culture studies and animal studies suggest that antioxidants can be used to fight oxidative damage hence decelerating the aging process, it is imperative to test those hypotheses in a clinical trial. 331 A recent study of 2570 women aged between 18 and 79 years found that Vitamin E is effective to maintain and grow higher skeletal muscle mass, which can eventually prevent sarcopenia. 332 Another randomized clinical trial conducted on 334 human beings suggested that Mediterranean diets containing olive oil and nuts can slow down age-related cognitive decline and decelerate the risk of developing dementia.…”
Section: Clinical Trial Of Antioxidantmentioning
confidence: 99%
“…To tackle the intracellular ROS homeostasis shift, cells use an array of antioxidant systems that are supported by certain cofactors and an exogenous supply of antioxidants. Although some cell culture studies and animal studies suggest that antioxidants can be used to fight oxidative damage hence decelerating the aging process, it is imperative to test those hypotheses in a clinical trial . A recent study of 2570 women aged between 18 and 79 years found that Vitamin E is effective to maintain and grow higher skeletal muscle mass, which can eventually prevent sarcopenia .…”
Section: Clinical Trial Of Antioxidantmentioning
confidence: 99%
“…Reactive oxygen species function like a double-edged sword in cancer progression, depending on their concentration in the cell and the stage of cancer. ROS have been reported to either enhance tumorigenesis and promote tumor progression by causing DNA damage and inducing pro-oncogenic pathways, or to induce cell death and apoptosis of cancer cells ( Shaito et al, 2020 ; Oyenihi et al, 2022 ; Oyenihi et al, 2022 ). To investigate whether OSEE exerts anti-proliferative effects on MDA-MB-231 cells through ROS generation, MDA-MB-231 cells were first pre-treated with NAC to dampen ROS generation, followed by treatment with OSEE at various concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…Reactive oxygen species function like a double-edged sword in cancer progression, depending on their concentration in the cell and the stage of cancer. ROS have been reported to either enhance tumorigenesis and promote tumor progression by causing DNA damage and inducing pro-oncogenic pathways, or to induce cell death and apoptosis of cancer cells (Shaito et al, 2020;Oyenihi et al, 3C). Figure 3C also shows that treatment with NAC augmented the inhibition of proliferation of MDA-MB-231 cells treated with lower concentrations of OSEE (50 and 100 μg/ml).…”
Section: Osee Has Potent Antioxidant Activity and Can Increase The Ge...mentioning
confidence: 99%
“…Apigenin inhibits the phosphorylation of ERK1/2 and FAK, which in turn encourages poor integrin synthesis and death. On the other hand, apigenin has also been observed to increase ERK expression in a few different tumor types (Cai et al, 2022; Che et al, 2020; Erdogan et al, 2020; Lee et al, 2019; Oyenihi et al, 2022). In conclusion, these findings support the notion that apigenin can induce apoptosis by deregulating MAPK/ERK signaling pathway in cancer cells.…”
Section: Cancer Therapeutic Potential Of Apigeninmentioning
confidence: 99%